1999
DOI: 10.1002/(sici)1097-0010(199908)79:11<1406::aid-jsfa378>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Processing of cauliflower by ohmic heating: influence of precooking on firmness

Abstract: The feasibility of processing cauliflower by ohmic heating was investigated. Firstly, cauliflower florets were precooked in tap water at low temperatures (40–70 °C) for 0 to 60 min. A control sample was cooked at 95 °C for 5 min. No significant textural differences were found between samples treated at 40 or 50 °C and fresh samples, but the firmness of samples cooked above 60 °C decreased. The effect of precooking time was not found to be significant. Secondly, low temperature precooking was performed in salte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…Spoilage was more than 5% after 28 days storage in all the treatments and such curds are not suitable for marketing. Similar trend in change of fi rmness were also reported by Eliot et al (1999) and Kudachikar et al (2007) in caulifl ower and banana, respectively.…”
Section: Introductionsupporting
confidence: 88%
“…Spoilage was more than 5% after 28 days storage in all the treatments and such curds are not suitable for marketing. Similar trend in change of fi rmness were also reported by Eliot et al (1999) and Kudachikar et al (2007) in caulifl ower and banana, respectively.…”
Section: Introductionsupporting
confidence: 88%
“…Wang & Sastry (1997) studied the effects of ohmic pretreatment and found no changes occurred in the moisture content of the final products. Eliot, Goullieux, & Pain (1999a) studied the influence of precooking by OH on the firmness of cauliflower. The results showed that OH combined with lowtemperature precooking in a saline solution is a viable alternative to HTST sterilization of cauliflower.…”
Section: Introductionmentioning
confidence: 99%
“…Wang and Sastry (1997) evaluated the effects of an ohmic pretreatment to vegetables and found no significant changes in the moisture content of the final product. Eliot et al (1999) studied the influence of precooking by OH on the firmness of cauliflower and concluded that OH combined with low-temperature precooking in saline solutions offers viable solution to HTST sterilization of cauliflower florets. In a study by Castro et al (2003), the suitability of several strawberry-based products to be processed by OH was tested.…”
Section: Introductionmentioning
confidence: 99%